Utilizing Youtube as A Digital Data Repository For The Development of Ethnochoreological Research Methods Through Archival Study and Netnography - Syahrial; Sriyadi; Galuh Widyaningtyas; Hartika (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
YouTube, as a digital media platform, offers significant potential as a source of non-field research data in ethnocoreology. Through access to audiovisual documentation, researchers can examine movement patterns, musical elements, costumes, and the performance contexts of dances across diverse ethnic traditions without geographical constraints. This study aims to explore the role of YouTube as a medium for ethnocoreological research through the integration of two methodological strategies: archival research and netnography. Within the archival research framework, YouTube is positioned as a cultural repository that preserves historical traces, aesthetic transformations, and evolving modes of dance presentation over time. In contrast, the netnographic approach views YouTube as a space of cultural interaction in which identity negotiation, meaning-making processes, and representational practices are enacted through the digital activities of virtual communities. This study employs a qualitative methodology, with ethnocoreology serving as the primary epistemological framework, thereby ensuring that dance analysis remains grounded in the relationship between textual and contextual dimensions. Data were collected from various YouTube features, including description boxes, comment sections, playlists, and community channels, and were supplemented by relevant scholarly literature. The findings indicate that YouTube functions not only as a medium for dance documentation but also as an epistemic arena that expands the research paradigm of ethnocoreology within the digital ecosystem. These findings underscore the importance of rigorous source criticism and stringent data selection procedures to ensure the scientific validity and reliability of research conducted through digital platforms.